2013
DOI: 10.1002/ange.201301265
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Si‐CHA Zeolite Layers Formed by a Selective Sonication‐Assisted Deposition Method

Abstract: Discrimination against the majority: The broad size distribution of conventional near‐cubic Si‐CHA (all‐silica chabazite) zeolites impedes the formation of a close‐packed layer, which is critical for the manufacture of zeolite films by secondary growth. Although present in lower abundance, platelike Si‐CHA particles cosynthesized with near‐cubic particles were deposited selectively on an α‐Al2O3 disk to form a uniform layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 36 publications
(35 reference statements)
2
15
0
Order By: Relevance
“…Both samples had a wide size distribution of ∼1−10 μm and some plate-like flakes, indicated by red arrows in Figure 1a, were also observed for CHA-L particles as similar to our previous report. 45 In addition, CHA-L and -H particle sizes were estimated by measuring the side length of the near cubic particles in the SEM images; the average sizes ± the corresponding standard deviations were estimated to be 4.6 ± 2.5 μm for CHA-L and 5.3 ± 2.6 μm for CHA-H (SI Figure S2). Despite the possible inaccuracy in estimating the particle sizes based on the SEM images, the wide size distributions of CHA-L and -H particles were evident.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both samples had a wide size distribution of ∼1−10 μm and some plate-like flakes, indicated by red arrows in Figure 1a, were also observed for CHA-L particles as similar to our previous report. 45 In addition, CHA-L and -H particle sizes were estimated by measuring the side length of the near cubic particles in the SEM images; the average sizes ± the corresponding standard deviations were estimated to be 4.6 ± 2.5 μm for CHA-L and 5.3 ± 2.6 μm for CHA-H (SI Figure S2). Despite the possible inaccuracy in estimating the particle sizes based on the SEM images, the wide size distributions of CHA-L and -H particles were evident.…”
Section: Resultsmentioning
confidence: 99%
“…First, siliceous CHA membranes were manufactured on α-Al 2 O 3 discs via conducting the secondary growth of Si-CHA seed layers. 45 Figure S7a,e) revealed that a continuous, but randomly oriented, CHA membrane (here, denoted as membrane CHA-L) was successfully synthesized by secondary growth. The SEM images in Figure 3b and SI Figure S7b−d indicated that CVD treatments up to 72 h at 200°C did not provide any noticeable change in the surface morphology as compared to membrane CHA-L (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pore size of this kind of zeolite, together with its selective adsorption properties, makes it promising for use in membranes to separate light hydrocarbon mixtures. Previously, SSZ-13 crystals [20,21] and membranes [22,23] were synthesized using N,N,N, trimethtyl-1-adamantammonium hydroxide (TMAdaOH) as the structure-directing agent (SDA). A SSZ-13 membrane with a CO 2 /CH 4 separation selectivity of 13 was firstly reported by Kalipcilar et al [23]; the membrane was prepared on the inside of porous stainless steel supports by two hydrothermal synthesis steps.…”
Section: Introductionmentioning
confidence: 99%
“…The seeded growth method relies greatly on a practical seeding route. Feasible seeding methods include dip-coating [7], rubbing [14], spin-coating [15], assembling [16], and ultrasonication method [2,17]. Sato and Nakane [18] tried the simplest dip-coating method and found it to bring highly reproducible fabrication of a high-flux NaA zeolite membrane.…”
Section: Introductionmentioning
confidence: 99%